Diarrhea in HIV Infection - Juferdy Kurniawan; Marcellus Simadibrata; Teguh Karyadi; Kie Chen (The Indonesian Society for Digestive Endoscopy, 2009)
During the last decade, there has been an increase of immunocompromized patients all around the world; that mostly due to pandemic of Human Immunodeficiency Virus (HIV) infection. Chronic diarrhea as one of common symptoms in patients with HIV infection has different etiology compared to immunocompetent patients. Initial approach of diarrhea in HIV infection may be conducted by evaluating the temporal relationship between the development of diarrhea and the administration of antiretroviral, especially the protease inhibitor agents; which is then followed by fecal analysis/examination for pathogenic bacteria and protozoa as well as endoscopy examination. Biopsy examination of intestinal mucosa is necessary for HIV enteropathy or diarrhea due to microsporidia, which is confirmed further by electron microscopy. The etiology of chronic diarrhea in HIV patients may also different, depend on the cluster of differentiation count value of all patients. Based on such differences, it is necessary to have adequate approach, recognition and understanding in the management of chronic diarrhea, especially for HIV patients. Keywords: diarrhea, infection, HI